Geography, institutions, and compared development in Africa - Luís Vaz Silva (University College Dublin, UCD School of Economics, 2007)
Recent years have seen a significant improvement in the economic performance of some African countries. The resulting increased dispersion in income levels across Africa, combined with the pertinence of detecting regional role models renders an intra-African analysis more attractive. In this paper I estimate the respective contribution of institutions, geography, and policies in determining income levels in sub-Saharan Africa. I find that income per capita in this region can be explained to a large extent with a few variables: quality of economic institutions, trade, population density in the 19th century, investment, mineral resources, and a dummy variable for small island nations. Contrary to other regions in the world, some policy variables remain significant after controlling for institutions in Africa. Measures of geography (climate, disease ecology, rainfall) have no direct effect on income levels once institutional quality is controlled for.
Keywords: 330; Volkswirtschaft; Wirtschaftswachstum; Sozialprodukt; Institutionelle Infrastruktur; Investitionspolitik; Rohstoffressourcen; Afrika südlich der Sahara